Factors of Incomplete Inpatient Medical Records Filling at Dr. H. Slamet Martodirdjo Regional General Hospital Pamekasan - Fajar, Achmad; Holipah, Holipah; Handayani, Ike (Jurnal Kedokteran Brawijaya, 2024)
Hospitals have an important role in improving health status by providing quality services, including complete medical record data and information. Complete and accurate medical records can be used for health care and patient treatment, evidence in law enforcement, medical discipline and medical ethics, educational and research purposes, basis of payment for health care costs, and health statistical data. This study aimed to identify the factors causing the incomplete filling of inpatient medical records at Dr. H. Slamet Martodirdjo Regional General Hospital Pamekasan. This research applied the descriptive observational method, with data collected through secondary data analysis using document studies and problem exploration using focus group discussions (FGD). The document study was conducted on 80 samples of inpatient medical records, while the FGD was conducted by inviting the head of the planning department, medical records officer, and 8 heads of inpatient wards to find out the causes and solutions for incomplete medical record files. The study results found that the number of incomplete medical records was 76.25%, with the highest percentage of incompleteness due to doctors, pharmacists, and nurses. The main problem causing the incompleteness of medical records was professional caregivers (PPA) who lacked discipline. The solutions obtained were management meetings and evaluations to professional caregivers, constructing policies that regulate reward and punishment systems, monitoring the checklists of medical record completeness, and routine evaluation of medical record files.